A framework of human system engineering applications and case studies - Handley, Holly A.; Tolk, Andreas (Wiley Professional, Reference & Trade, 2020)
This book presents a series of Human System Engineering (HSE) applications on a range of topics, such as interface design, training requirements, personnel capabilities and limitations, and human task allocation. Each chapter represents a case study of the application of HSE from different dimensions of socio-technical systems. The examples are organized using a socio-technical system framework to reference the applications across multiple system types and domains. These case studies serve to illustrate the value of applying HSE to the broader engineering community and provide real world examples. The book provides reference examples in a variety of domains and applications to educate engineers; the integration of the human user is listed as one of the enablers of System Engineering (SE) in the System Engineering Body of Knowledge (SEBoK).